2015
DOI: 10.1021/acs.est.5b00253
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Digital Polymerase Chain Reaction (PCR) Outperforms Real-Time PCR in the Detection of Environmental DNA from an Invasive Fish Species

Abstract: Environmental DNA (eDNA) has been used to investigate species distributions in aquatic ecosystems. Most of these studies use real-time polymerase chain reaction (PCR) to detect eDNA in water; however, PCR amplification is often inhibited by the presence of organic and inorganic matter. In droplet digital PCR (ddPCR), the sample is partitioned into thousands of nanoliter droplets, and PCR inhibition may be reduced by the detection of the end-point of PCR amplification in each droplet, independent of the amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
155
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(164 citation statements)
references
References 41 publications
6
155
3
Order By: Relevance
“…ddPCR has superior precision over other detection technologies to detect differential expression in miRNAs [39]. Additionally, ddPCR is more resilient to sample quality differences; has a high tolerance to PCR amplification inefficiency; and requires small sample size, which allows for high level of precision being able to capture all known sources of variation [39, 40]. …”
Section: Resultsmentioning
confidence: 99%
“…ddPCR has superior precision over other detection technologies to detect differential expression in miRNAs [39]. Additionally, ddPCR is more resilient to sample quality differences; has a high tolerance to PCR amplification inefficiency; and requires small sample size, which allows for high level of precision being able to capture all known sources of variation [39, 40]. …”
Section: Resultsmentioning
confidence: 99%
“…At higher concentrations (>200 copies/μL), recent research has shown that qPCR and ddPCR are equivalent at detecting eDNA 37 however, ddPCR can detect eDNA significantly better at very low concentrations (<3 copies/mL) 12, 25, 38 . Using the same primers and Taqman probe from qPCR, target DNA was randomly allocated on to discrete droplets using microfluidics and then each of the samples, containing 10,000 to 20,000 nanodroplets via microfluidics that are then thermally-cycled (see Nathan et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the pond experiment, we failed to find any significant differences in the detection rate of carp eDNA by the two precipitation methods, when the reaction volume was the same, perhaps because the detection rate was only determined by the presence or absence of a few copies of target eDNA (Doi et al ). However, in samples with low eDNA concentrations, the isopropanol precipitation method would exhibit a higher detection rate, owing to a higher amount of recovered eDNA.…”
Section: Discussionmentioning
confidence: 88%
“…The environmental DNA (eDNA) method can be used to estimate the distribution of aquatic organisms, using DNA extracted from the water of aquatic habitats (Ficetola et al ; Rees et al ; Goldberg et al ; Thomsen and Willerslev ). Since the eDNA method is an easy‐to‐use approach, which only requires collecting water from the field, it has been applied to diverse species in various ecosystems, including ponds and lakes (e.g., Ficetola et al ; Thomsen et al ; Jerde et al ; Takahara et al ; Doi et al ; Uchii et al ), rivers (Minamoto et al ; Pilliod et al ; Fukumoto et al ; Wilcox et al ; Yamanaka and Minamoto ), and marine habitats (Mahon et al ; Miya et al ; Yamamoto et al ).…”
mentioning
confidence: 99%